Faktor-Faktor yang Berhubungan dengan Prestasi pada Atlet Atletik dan Sepak Bola di SKO Ragunan Jakarta tahun 2025: Factors Associated with Performance in Athletics and Football Athletes at SKO Ragunan, Jakarta, 2025 - Sarah Zahrani Chandra; Sintha Fransiske Simanungkalit; Nur Intania Sofianita (Amerta Nutrition, 2025)
Background: Athletics and football are sports disciplines in Indonesia in which performance continues to fluctuate. This condition represents an important concern for the respective sports disciplines to identify strategies to maintain optimal athlete performance so that achievements can consistently improve. Objectives: This study aimed to analyze factors associated with performance among athletics and football athletes. Methods: This study employed a cross-sectional design with a sample of 103 athletics and football athletes enrolled in grades 7–12 at SKO Ragunan. Total sampling was applied using inclusion and exclusion criteria, namely athletes from athletics and football, in good health, and willing to participate as study respondents. Data analysis was conducted using the Chi-square test. Results: Bivariate analysis showed an association between physical fitness (p-value=0.001), lower limb muscle endurance (p-value=0.002), and body fat percentage (p-value=0.013) with athlete performance, while no association was found between doping knowledge (p-value=0.183) and branched-chain amino acid (BCAA) consumption (p-value=0.099) with performance among athletics and football athletes at SKO Ragunan, Jakarta. Conclusions: Physical fitness, lower limb muscle endurance, and body fat percentage were associated with performance among athletics and football athletes at SKO Ragunan, Jakarta, whereas doping knowledge and BCAA consumption showed no significant association.